Kecurangan dan Perlindungan Konsumen Asuransi - Sendra, Ketut (Jurnal Vokasi Indonesia, 2017)
Establishing a national economy that can grow suatainably and stable, requires the financial service sectors conducting its business in a well organized, fair, transparent and accountable manner, and be able to protect the consumer’s and public’s interests. Transparency, fairness, reliability, confidentiality, security of consumer’s data and/or information, fast, simple complaint handling and affordable dispute resolution cost become the principles of consumers protection in the financial services sector. The common motive to conduct an insurance fraud is economical reason, that is for obtaining a financial benefit/advantage. Broadly, a fraud in insurance can be classified into 3 (three) main dimensions: dimension of the subject i.e the fraudsters; dimension of time, ie. the time during the process of underwriting and the process of claim; dimension of behaviour that is opportunistic act (soft fraud) or planned fraud (hard fraud). The insurance consumer’s awareness concerning the financial services sector activities is needed, so that the insurance financial services sector can be conducted in a well organized, fair, transparent, and accountable manner